2007
DOI: 10.3181/0701-rm-112
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Response of Splanchnic Arteries from Cirrhotic Patients: Role of Nitric Oxide, Prostanoids, and Reactive Oxygen Species

Abstract: Peripheral and splanchnic vasodilatation in cirrhotic patients has been related to hyporesponsiveness to vasoconstrictors, but studies to examine the vascular adrenergic response provide contradictory results. Hepatic arteries from cirrhotic patients undergoing liver transplantation and mesenteric arteries from liver donors were obtained. Segments 3 mm long from these arteries were mounted in organ baths for testing isometric adrenergic response. The concentration-dependent contraction to noradrenaline (10(-8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
4
2
0
Order By: Relevance
“…There were significant differences regarding the logEC 50 values spanning three orders of magnitude indicating large differences in mesenteric artery sensitivity to the contractile effects of AVP, ET-1 and NE which is in agreement with the available literature (24)(25)(26)(27). In studies reporting poor phenylephrine responsiveness of human mesenteric arteries (28) and in the present study, patients were older than in studies reporting maximum vasoconstrictor effects close to or exceeding high potassium-induced rises in wall tension (25,29). Our data suggest that 2 -adrenoceptors mediate to a large extent the NEinduced constrictions in human mesenteric arteries.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There were significant differences regarding the logEC 50 values spanning three orders of magnitude indicating large differences in mesenteric artery sensitivity to the contractile effects of AVP, ET-1 and NE which is in agreement with the available literature (24)(25)(26)(27). In studies reporting poor phenylephrine responsiveness of human mesenteric arteries (28) and in the present study, patients were older than in studies reporting maximum vasoconstrictor effects close to or exceeding high potassium-induced rises in wall tension (25,29). Our data suggest that 2 -adrenoceptors mediate to a large extent the NEinduced constrictions in human mesenteric arteries.…”
Section: Discussionsupporting
confidence: 90%
“…There were significant differences regarding the logEC 50 values spanning three orders of magnitude indicating large differences in mesenteric artery sensitivity to the contractile effects of AVP, ET-1 and NE which is in agreement with the available literature (24)(25)(26)(27). We found that the three physiological vasoconstrictors tested induced similar maximum increases in wall tension.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our results in mice and rats, these data support a role for α 1 AR in modulating vasoconstriction to adrenergic activation. Mesenteric arteries from patients with cirrhotic liver disease displayed robust vasoconstriction to NE that could be attenuated by prazosin, but not yohimbine, an α 2 antagonist [75]. Although these data are in line with our observation in rats (α 1A AR activity without much evidence for α 2 AR activation), the study was lacking a nondiseased control group for comparison.…”
Section: Discussion/conclusionsupporting
confidence: 77%
“…Major surgery in patients who already have a tendency towards vasodilatation, such as cirrhotic patients undergoing liver transplantation, is associated with a frequent requirement for intra‐operative administration of either inotropes or vasopressors [5, 13, 14]. Although a previous study has suggested that the response to vasoconstrictors may be blunted in cirrhosis [15], other more recent studies have disputed this [16, 17]. Noradrenaline and phenylephrine are the most commonly used vasopressors in modern clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are few reports in the literature, phenylephrine is also frequently used during liver transplantation. It has been shown to cause vasoconstriction in mesenteric and hepatic arteries in cirrhotic patients [17].…”
Section: Discussionmentioning
confidence: 99%